PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TAKING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - Yunita, Sesma; Aima, Zulfitri; Harisman, Yulyanti (Pendidikan Matematika, 2013)
The background of this research is the lower ability comprehension of mathematical concept for students. The students on the study math are out of focus and not concentration. The purpose of this research is to determine whether ability comprehension of mathematical concept for students by applying active learning strategyâs type Guided Note Taking were better than implementasi of conventional learningâs students for grade VIII SMPN 2 lingggo Sari Baganti regency of South Beach. The type of research is experimental by using Random toward subject. The instrument of this research is the comprehension of mathematical concept test. The technique of data analysis is using t-test one side with help Minitab. Based on the data analysis results have sampel class distribution normal and homogeneous to level Î±. The result that obtained P-value = 0,030 Î± then this research is accepted hypothesis. Inferential that the ability comprehension of mathematical concept for student by applying active learning strategyâs type Guided Note Taking is better than implementasi conventional learningâs students for grade VIII SMPN 2 lingggo Sari Baganti regency of South Beach.